Socially facilitative robots for older adults to alleviate social isolation: A participatory design workshop approach in the US and Japan - Fraune, Marlena R.; Komatsu, Takanori; Preusse, Harrison R.; Langlois, Danielle K.; Au, Rachel H. Y.; Ling, Katrina; Suda, Shogo; Nakamura, Kiko; Tsui, Katherine M. (Frontiers in Psychology, 2022)
Social technology can improve the quality of older adults’ social lives and mitigate negative mental and physical health outcomes associated with loneliness (Fees et al. 1999), but it should be designed collaboratively with this population. In this paper, we used participatory design (PD) methods to investigate how robots might be used as social facilitators for middle-aged and older adults (age 50+) in both the US and Japan. We conducted PD workshops in the US and Japan because both countries are concerned about the social isolation of these older adults due to their rapidly aging populations. We developed a novel approach to participatory design of future technologies that spends 2/3 of the PD session asking participants about their own life experiences as a foundation. This grounds the conversation in reality, creates rapport among the participants, and engages them in creative critical thinking. Then, we build upon this foundation, pose an abstract topic, and ask participants to brainstorm on the topic based on their previous discussion. In both countries, participants were eager to actively discuss design ideas for socially facilitative robots and imagine how they might improve their social lives. US participants suggested design ideas for telepresence robots, social distancing robots, and social skills artificial intelligence programs, while Japanese participants suggested ideas for pet robots, robots for sharing experiences, and easy-to-operate instructor robots. Comparing these two countries, we found that US participants saw robots as tools to help facilitate their social connections, while Japanese participants envisioned robots to function as surrogate companions for their parents and distract them from loneliness when they were unavailable. With this paper, we contribute to the literature in two main ways, presenting: 1) A novel approach to participatory design of future technologies that grounds participants in their everyday experience, and 2) Results of the study indicating how middle-aged and older adults from the US and Japan wanted technologies to improve their social lives. Although we conducted the workshops during the COVID-19 pandemic, many findings generalized to other situations related to social isolation, such as older adults living alone.